Dehydroabietic Acid Derivative QC4 Induces Gastric Cancer Cell Death via Oncosis and Apoptosis. (29th February 2016) - Luo, Dongjun; Ni, Qing; Ji, Anlai; Gu, Wen; Wu, Junhua; Jiang, Chunping
Abstract : Aim . QC4 is the derivative of rosin's main components dehydroabietic acid (DHA). We investigated the cytotoxic effect of QC4 on gastric cancer cells and revealed the mechanisms beneath the induction of cell death. Methods . The cytotoxic effect of QC4 on gastric cancer cells was evaluated by CCK-8 assay and flow cytometry. The underlying mechanisms were tested by administration of cell death related inhibitors and detection of apoptotic and oncosis related proteins. Cytomembrane integrity and organelles damage were confirmed by lactate dehydrogenase (LDH) leakage assay, mitochondrial function test, and cytosolic free Ca 2+ concentration detection. Results . QC4 inhibited cell proliferation dose- and time-dependently and destroyed cell membrane integrity, activated calpain-1 autolysis, and induced apoptotic protein cleavage in gastric cancer cells. The detection of decreased ATP and mitochondrial membrane potential, ROS accumulation, and cytosolic free Ca 2+ elevation confirmed organelles damage in QC4-treated gastric cancer cells. Conclusions . DHA derivative QC4 induced the damage of cytomembrane and organelles which finally lead to oncosis and apoptosis in gastric cancer cells. Therefore, as a derivative of plant derived small molecule DHA, QC4 might become a promising agent in gastric cancer therapy.